PENINGKATAN KEMAMPUAN GURU DALAM PEMBUATAN KELENGKAPAN PERANGKAT PEMBELAJARAN MELALUI SUPERVISI KEPALA SEKOLAH - Sukirman Sukirman (LPPM UNISDA, 2020)
This research aimed to improve the ability of teachers in making the completeness of learning devices. This action research is done by following the main flow: initial reflection, planning, action execution, observation, reflection, and redesign. The results showed that classroom supervision activities can improve the ability of teachers in the ability of teachers in making the completeness of learning devices and managing the class administration in Badurame I State Elementary School, Turi sub- district, Lamongan.